Application of Local knowledge in land degradation Assessment in the Bakwu East Municipality. - Kusimi, J.M.; Yiran, G.A.B. (Department of Geography and Resource Development, University of Ghana, 2011)
A number of scientific methodologies have been used in assessing land degradation globally. However, the use of local knowledge in eliciting indicators of land degradation has seen little application by scientists and policy makers. Researchers believe the two approaches could complement each other to provide a holistic assessment of land degradation. The objective of the study was to find out local approaches used in assessing land degradation by farmers of the Bawku Municipality. Secondly, we investigated farmers’ perception of the causes of the problem and their coping strategies. The study was conducted using questionnaire interviews and focus group discussions. Farmers perceived degradation in the soil and vegetation which is explained by population growth, bush burning, overgrazing, fuel wood harvesting, expansion of farm land and drought. Degradation in the soil and vegetation took the form of soil erosion, soil compaction, loss in soil fertility and deforestation. The lack of proper coordination among stakeholders (farmers, Non-governmental Organizations and Local authorities) in the locality has resulted in poor planning and implementation of land degradation intervention measures. Also, some intervention measures are instituted without public consultations, hence the unwillingness of the people to implement them. The primary effect of land degradation include scarcity of wood products for building and domestic energy supply, less pasture for animals and low crop yield which worsens the poverty and hunger amongst the people. The strategies for coping with this environmental challenge include inorganic fertilizer application, organic manure application, diversification of crops, planting of early maturing/drought tolerant crops, dry season gardening/irrigation and mixed cropping
Keywords: Bawku, Land degradation, Local knowledge on land degradation, Farmers’ perception regarding land degradation